Ali bin Al- Rand revolution in the city of Gafsa and the position of the Al- Mohadeen (572- 576 A.H/ 1176- 1181 A.D) "Historical study" - Al- Khliefat, Mohammad Atallah (Journal of Humanities & Social Sciences, 2020)
The Al- Mohadia state was exposed to many revolutions against its rule, whether in the countries of Morocco, Africa or Al- Andalus. these revolutions have contributed significantly to weaken the state and its preoccupation with the dangers facing them, especially the Christian recovery movement in Andalusia. this study came to address one of those revolutions, a revolution Ali bin Al- Rand in the city of Gafsa. this study dealt with the geography of Gafsa, the origin of the sons of Rand and how they established their emirate in Gafsa. the study also dealt with how the princes of Bani Al- Rand and Gafsa enter the obedience of Al- Mohadeen. Then it showed the factors of the revolution its motives and how the caliph Abu Yaqoub Al- Mohade was able to eliminate them. The study concluded to reach a number of results, the most important of which is that the revolution showed despite its failure the extent of love and loyalty of the people of Gafsa to the family of Bani Al- Rand, and their preference for autonomy to submit to obedience to the Al- Mohadeen. The study relied on the historical research methodology in terms of relying on original sources, documentation and closer reading. It also use of analysis, extraction, criticism and comparison as allowed by the research framework.